U.S. News Coverage of Transgender Victims of Fatal Violence: An Exploratory Content Analysis - Osborn, Max (Violence against women, 2022)
Media portrayals of crime help shape public perceptions of victims and the demographic groups to which they belong. For transgender people, who already face heightened disparities and stigma, news coverage may reinforce negative stereotypes and minimize the wider context of transphobic violence. The present study, a content analysis of news articles (n = 316) pertaining to 27 transgender people killed in the United States in 2016, addresses positive and negative depictions of victims, use of language affirming and delegitimizing transgender identities, and framing of transphobia as a systemic problem. Themes, implications, and future research directions are discussed.